A correlational analysis investigating relationships between gender role ideology and attitudes towards gender-based violence - Krutani, Siposetu (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
This study forms part of a larger project investigating attitudes towards intimate partner violence, dating violence and other forms of gender-based violence with the Rhodes University context. The primary purpose was to establish a baseline descriptive understanding of participants"Ÿ attitudes towards and perceptions of gender-based violence. With the aim to generate results that would somehow inform the larger project, the current study sought to investigate whether a relationship exists between gender-role ideology and attitudes towards gender-based violence amongst a university population which was inclusive of registered students and employees of the university (n = 308). Four samples were categorised: student sample, academic staff sample, administrative support staff sample and operational support staff sample. A once-off, cross sectional survey design was used to obtain the data. The results of the study revealed that the participants in the study uphold largely non-traditional gender-role ideologies, are generally intolerant of dating violence and are rejecting of rape myths. As predicted in the literature, the study revealed that demographics such as gender, religion, age, level of education, number of years spent in the institution, race, and student accommodation have an impact on the relationship between adherence to traditional gender-role ideology and tolerance towards dating violence, as well as on the relationship between adherence to traditional gender-role ideology and rape myth acceptance and the relationship between rape myth acceptance and tolerance towards dating violence. The study contributes to the growing body of knowledge on gender-based violence in institutions of higher learning and could help improve sexual violence prevention programmes in such contexts.
Keywords: Women -- Violence against -- South Africa; Sex role -- Psychological aspects -- South Africa; Male domination (Social structure) -- South Africa; Rhodes University -- Students -- Attitudes; Rape in universities and colleges -- South Africa; Social movements -- South Africa -- Makhanda; Women college students -- Violence against -- South Africa; Male college students -- South Africa -- Attitudes; Women college students -- Psychology -- South Africa; Male college students -- Psychology -- South Africa